Effect of Topical Antibiotic around Implant Cover Screw on the Prevention of Crestal Bone Resorption Using Fractal Analysis: A Randomized Clinical Trial - Naser Sargolzaie; Hossein Hoseini Zarch; Seyed Ali Banihashemrad; Mohammad Halimi Makou; Shabnam Ganjehzadeh (Mashhad University of Medical Sciences, 2022)
The presence of peri-implant inflammation can lead to the loss of implant if extended to the bone. Therefore, it is essential to develop effective strategies for the prevention and treatment of diseases around the implant. The present study aimed to assess the effect of topical antibiotics on the prevention of implant crestal bone resorption using fractal analysis. Methods: A total of 30 patients with a mean age of 41.4 ±4.2 years and in need of dental implants were randomly assigned to three groups (n=10). The first and second test groups received 0.5% erythromycin ointment and 0.3% gentamicin, while the control group received no antibiotics. To evaluate the degree of crestal bone resorption around dental implants at baseline and three months later, a phosphor plate radiograph was taken and fractal analysis was then performed to determine the degree of resorption. Results: The comparison with the fractal changes between the two time intervals demonstrated that there were no significant differences in all three groups (P>0.05). There was a significant difference among the three groups in the fractal dimension (FD) index just after the implant placement (P=0.03). The control group was significantly different from the erythromycin and gentamicin groups in terms of FD index immediately after implant placement. Nonetheless, there was no significant difference between the erythromycin and gentamicin groups (P=0.07). There was no significant difference in FD among the three groups three months after implant placement. Conclusion: Using topical antibiotics did not affect bone resorption after three months of implant placement.